Evaluation on potential application of lipase immobilized on rice husks in enzymatic glycerolysis reaction - Cieh, Ng Lin; Mokhtar, Mohd Noriznan; Baharuddin, Azhari Samsu; Mohammed, Mohd Afandi P.; Nor, Mohd Zuhair Mohd; Wakisaka, Minato (Elsevier, 2024)
Owing to high production cost and low reaction yield, immobilized lipase is rarely used in industrial glycerolysis. This research characterizes the performance of lipase immobilized on rice husk in glycerolysis reaction. By utilizing hexamethylenediamine (HMDA) and glutaraldehyde (GA) as coupling agents, lipase from Thermomyces lanuginosus was immobilized on oxidized rice husk (ORH). For comparison, another sample was prepared where the lipase was directly immobilized on ORH without the use of HMDA and GA. Then, monoglyceride production was performed via glycerolysis using the immobilized lipase. The FTIR analysis verify interactions on rice husk including rice husk oxidation, HMDA coupling, GA activation and lipase immobilization on rice husk. The study found that within the examined range of added lipase for immobilization (10–40 mg-protein/g-support), ORH–HMDA–GA–Lipase possessed superior outcomes in terms of protein loading, immobilization yield, and recovered glycerolysis activity compared to ORH–Lipase. Besides, ORH–HMDA–GA–Lipase exhibits better storage stability (60°C, 44.9 %) and higher reusability (90.0 % monoglyceride yield at the 8th cycle) against ORH–Lipase. The results confirm satisfying performance of the prepared immobilized lipase in glycerolysis and highlight its enhancements facilitated by coupling agents.